Validation of immunoglobulin G enzyme-linked immunosorbent assay for antibodies to pneumococcal surface adhesin A in the diagnosis of pneumococcal pneumonia among adults in Kenya. - Scott, J; Obiero, J; Hall, A; Marsh, K (2002)
Epidemiologic studies of pneumococcal pneumonia, including vaccine efficacy trials, are hampered by a lack of sensitive and specific diagnostic tests. Pneumococcal surface adhesin A (PsaA) is a genetically conserved, surface-expressed protein common to all serotypes of Streptococcus pneumoniae and is highly immunogenic. Detection of anti-PsaA immunoglobulin G by recombinant PsaA enzyme-linked immunosorbent assay was evaluated for diagnosis of pneumococcal pneumonia in paired serum samples from 4 adult populations: 47 healthy control subjects, 56 clinic control subjects without pneumococcal disease syndromes, 109 patients with pneumococcal pneumonia, and 93 pneumonia patients with no evidence of pneumococcal etiology. By considering a 2-fold increase in antibody concentration as positive, sensitivity was 0.70, and specificity was 0.98. With a 1.3-fold increase, these were 0.89 and 0.98, respectively. The test's performance was not affected by the patients' human immunodeficiency virus status or by the pneumococcal serotype. The combination of high sensitivity and high specificity makes this an ideal assay for epidemiologic studies of pneumococcal pneumonia.